The Role of The School Literature Movement in Increasing Reading Interest in Elementary School Students : GLS, Interest in reading, Elementary school - Nafiah; Suharmono Kasiyun; Syamsul Ghufron; Yulianti (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Abstract: This study aims to describe the School Literacy Movement in increasing reading interest of elementary school students. This study uses a qualitative approach to the type of media discourse study research The population used is a written document regarding the School Literacy Movement research in increasing reading interest of elementary school students. The written documents are in the form of books and journal articles. The data collection technique used is the documentation technique in the form of articles on google scholar. Data analysis used Miles, Huberman and Saldana models, namely data collection, data condensation, data display, and conclusion drawing / verification. The results showed that: 1) the implementation of the School Literacy Movement  was carried out in 3 stages, namely the habituation stage, the development stage, and the learning stage. 2) based on the results of the analysis on the School Literacy Movement, it can increase the reading interest of elementary school students. 3) there are inhibiting factors and supporting factors in the application of the School Literacy Movement in increasing reading interest of elementary school students.